If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3 + 2x + -9 = 9 Reorder the terms: -3 + -9 + 2x = 9 Combine like terms: -3 + -9 = -12 -12 + 2x = 9 Solving -12 + 2x = 9 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '12' to each side of the equation. -12 + 12 + 2x = 9 + 12 Combine like terms: -12 + 12 = 0 0 + 2x = 9 + 12 2x = 9 + 12 Combine like terms: 9 + 12 = 21 2x = 21 Divide each side by '2'. x = 10.5 Simplifying x = 10.5
| -10(3+2)-7= | | 569.7844=3135.6289h | | v+4=3v-6 | | 2=-2x+25 | | -7x=-16 | | 12+x-2x=-4+x | | 5s-11=13+s | | f(x+7)=x^2+8x+5 | | -7-7x=-16 | | 12x+6=x | | 5v-2=2+2v-2+1 | | -18=-2+2w | | 6n-7=n+3 | | 2m+11=33 | | .40x+0.06(30)=9.8 | | -8+x+3x=-8+4x | | 14x=2x^2-16 | | 7=3+16q | | -4=3x-5(x+1) | | G(-x)=3x^2-3x+5 | | S^6-t^6=(s^2)3-(t^2)3 | | 35x+y=1230 | | 2x+3y+z=22 | | 6x+14=-42-2x | | 2(6y-5)=20 | | 2(x+4)-x=11 | | N-64=312 | | 0.222x+0.6667x=7 | | -15+5m=7m-5m | | x+1=4x+6-3x | | (4x+2)-x=11 | | 1=8n-9 |